The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1085/jgp.90.3.361
|View full text |Cite
|
Sign up to set email alerts
|

Guanidinium analogues as probes of the squid axon sodium pore. Evidence for internal surface charges.

Abstract: A B S T R A C T We have investigated the reduction of steady state sodium channel currents by a monovalent and a divalent guanidinium analogue. The amount of block by the divalent compound at a constant membrane potential was dramatically reduced by an increase in the internal salt concentration. Channel block by the monovalent molecule was a less steep function of salt concentration. These results would be expected if there were negative charges near the sodium pore that produced a local accumulation of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Based on results on sodium channel gating obtained with the squid giant axon (Chandler et al, 1965) and frog myelinated nerve (Hille et al, 1975), the extracellular and intracellular channel (or membrane) surfaces appear to differ in apparent charge density. (In fact, the charge distribution at either surface is likely to be inhomogeneous, as Smith-Maxwell and Begenisich [1987] found that the apparent charge density in the vicinity of the intracellular channel entrance in the squid giant axon differed approximately fourfold from the charge density deduced from gating experiments.) With respect to channel gating, the apparent charge density at the extracellular surface was estimated to be three to five times larger than that of the intracellular surface (Hille et al, 1975).…”
Section: Channel Asymmetry and Electrolyte-dependent Gating Shiftsmentioning
confidence: 99%
“…Based on results on sodium channel gating obtained with the squid giant axon (Chandler et al, 1965) and frog myelinated nerve (Hille et al, 1975), the extracellular and intracellular channel (or membrane) surfaces appear to differ in apparent charge density. (In fact, the charge distribution at either surface is likely to be inhomogeneous, as Smith-Maxwell and Begenisich [1987] found that the apparent charge density in the vicinity of the intracellular channel entrance in the squid giant axon differed approximately fourfold from the charge density deduced from gating experiments.) With respect to channel gating, the apparent charge density at the extracellular surface was estimated to be three to five times larger than that of the intracellular surface (Hille et al, 1975).…”
Section: Channel Asymmetry and Electrolyte-dependent Gating Shiftsmentioning
confidence: 99%
“…The open channel current obtained in the presence of a blocking divalent cation, I, was fit to the following relation (Smith-Maxwell and Begenisich, 1987;MacKinnon et al, 1989),…”
Section: Ion Channel Blockade and Surface Chargementioning
confidence: 99%
“…Surface potential is the potential difference between the membrane surface and the bulk aqueous phase and is dependent on the density of interfacial charged molecules (for a review see McLaughlin, 1989). In biological membranes, this potential is on the order of a few tens of mV and might have an important role in affecting the conductance of channels in the membrane (Dani, 1986;Jordan, 1987; Kell and DeFelice, 1988), determining the structure of proteins (Gilson and Honig, 1988;Honig et al, 1986;Huang and Warshel, 1988;Perutz, 1978) and in the binding of charged molecules to the membrane (Green and Andersen, 1986;Green et al, 1987;Smith-Maxwell and Begenisich, 1987). impact on cell membrane biology is not well appreciated.…”
Section: Introductionmentioning
confidence: 99%